1989
DOI: 10.1111/j.1365-2621.1989.tb00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of acid‐catalysed de‐esterification of pectin in a heterogeneous medium

Abstract: The rate constants of acid-catalysed de-esterification at 30,40 and 50°C of apple, lemon, grapefruit, orange and carrot pectins, in ethanolic hydrochloric acid show that the reaction is a pseudo first-order reaction and is uninfluenced by the origin of the pectin.The activation parameters (AS* = -107.2f2.6 J mol-' K-'; AH* = 74.51k0.96 kJ mol-') were close to those calculated by Speiser, Eddy and Hills (1945) for homogeneous acid de-esterification of apple pectin, and thus the reaction mechanism appears to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…The higher yield was obtained when BPP were extracted under acidic conditions (Fig. 2a), possibly because the acid enhanced cell wall disruption and hence increase pectin release (Kirtchev et al 1989).…”
Section: Resultsmentioning
confidence: 99%
“…The higher yield was obtained when BPP were extracted under acidic conditions (Fig. 2a), possibly because the acid enhanced cell wall disruption and hence increase pectin release (Kirtchev et al 1989).…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained are supported by Yeoh et al (2008) who reported that orange peel pectin yield increased by 4.5% at pH 1 using microwave extraction. The increase in pectin yield was because of the acid-enhanced cell wall disruption and hence increases pectin release (Kirtchev et al 1989). A lower pH enhanced the release of glucose from starch hydrolysis and disintegrated the polysaccharides that could co-precipitate with pectin in ethanol.…”
Section: Extraction Of Ppp Pectinmentioning
confidence: 99%
“…Alkalibehandlung) als auch enzymatische Methoden beschrieben, bei denen die Freisetzung durch unterschiedliche Methyl-, Acetyl-bzw. Ferulasäureesterasen erfolgt (Kirtchev et al 1989;El-Nawawi und Heikal 1995;Renard und Thibault 1996;De Vries et al 2002;Kim et al 2008;Gou et al 2012; Müller-Maatsch et al…”
Section: Modifikation Des Veresterungsgrads Durch Alkalibehandlungunclassified